Noise controlled semiconductor optical amplifier based on lateral cavity laser - (:unkn) unknown (My University, 2010)
Experimental characterisation of a novel noise-controlled semiconductor optical amplifier (NCSOA) is presented. The design utilises grooves etched parallel to the active waveguide, at the output sections of the NCSOA, so as to induce lasing laterally to the propagation axis. This clamps the carrier density in a relevant region, allowing for the engineering of a specific longitudinal carrier density profile, corresponding to an improved noise figure performance. Results have demonstrated the effectiveness of carrier density profile engineering as a means of reducing the noise figure in semiconductor optical amplifiers.
PUBLISHED
Keywords: Carrier density; Laser cavity resonators; Laser noise; Semiconductor optical amplifiers; Waveguide lasers